Dynamic response of polymethacrylimide foam sandwich structures with different core layers under water impact loading - Peilin Zhu; Jili Rong; Shenglong Wang; Zichao Chen; Zifan Jiang (Defence Technology)
Polymethacrylimide (PMI) foam has the highest specific stiffness and strength among polymer foams, with excellent radar-absorbing capabilities, which provide it with broad prospects in underwater applications. To evaluate the impact resistance of PMI foam sandwich structures, the dynamic response and energy absorption characteristics of PMI foam sandwich structures with different core layers under various water impact loads were investigated using combined experimental and numerical methods. A fluid-structure interaction device with a diffusion angle was used for water impact testing of the PMI foam sandwich structures. The 3D-DIC technique was employed to process the deformation images of the sandwich-structure back panel captured by the high-speed cameras. Numerical simulations were performed to analyze the dynamic deformation process of the PMI foam core. The results indicated that the maximum deformation of the back panel exhibited a nonlinear relationship with the impulse. Below the critical impulse, the maximum deformation of the back panel plateaued, which was determined by the core density. Beyond the critical impulse, the rate of deformation increased with the impulse was governed by the core thickness. Compared with different sandwich panels, PMI foam sandwich structures demonstrate significant advantages in terms of impact resistance under high-impulse conditions.